A database solution for the quantitative characterisation and comparison of deep-marine siliciclastic depositional systems. (April 2019) - Cullis, Sophie; Patacci, Marco; Colombera, Luca; Bührig, Laura; McCaffrey, William D.
Abstract: Comparative analyses of deep-marine sedimentological studies are hindered by the wide variety in methods of data collection, scales of observation, resolution, classification approaches and terminology. A relational database, the Deep-Marine Architecture Knowledge Store (DMAKS), has been developed to facilitate such analyses, through the integration of deep-marine sedimentological data collated to a common standard. DMAKS hosts data on siliciclastic deep-marine system boundary conditions, and on architectural and facies properties, including spatial, temporal and hierarchical relationships between units at multiple scales. DMAKS has been devised to include original and literature-derived data from studies of the modern sea-floor, and from ancient successions studied in the subsurface and in outcrop. The database can be used as a research tool in both pure and applied science, allowing the quantitative characterisation of deep-marine systems. The ability to synthesise data from several case studies and to filter outputs on multiple parameters that describe the depositional systems and their controlling factors enables evaluation of the degree to which certain controls affect sedimentary architectures, thereby testing the validity of existing models. In applied contexts, DMAKS aids the selection and application of geological analogues to hydrocarbon reservoirs, and permits the development of predictive models of reservoir characteristics that account for geological uncertainty. To demonstrate the breadth of research applications, example outputs are presented on: (i) the characterisation of channel geometries, (ii) the hierarchical organisation of channelised and terminal deposits, (iii) temporal trends in the deposition of terminal lobes, (iv) scaling relationships between adjacent channel and levee architectural elements, (v) quantification of the likely occurrence of elements of different types as a function of the lateral distance away from an element of known type, (vi) proportions and transition statistics of facies in elements and beds, (vii) variability in net-to-gross ratios among element types. Highlights: A repository for deep-marine sedimentological data has been built, known as DMAKS. Data standardisation enables quantitative analysis of deep-marine systems. Multi-parameter querying aids evaluation of deep-marine boundary condition effects. DMAKS output can be used to produce predictive models of sedimentary architecture. DMAKS can be used to produce synthetic analogues to hydrocarbon reservoirs.